Editorial for the Special Issue “Phytotoxicity of Heavy Metals in Contaminated Soils” - Ana Romero-Freire; Manuel Sierra-Aragón; Hao Qiu; Erkai He (Toxics, 2023)
Soil is an essential natural resource because of the ecosystem services it carries out in the terrestrial ecosystem: the provision of food, fibre and fuel; habitats for organisms; nutrient cycling; climate regulation and carbon sequestration; water purification and soil contaminant reductions; and others [...]